Adult Right Living‐Donor Liver Transplantation With Special Reference to Reconstruction of the Middle Hepatic Vein. Issue 12 (13th November 2014) - Akamatsu, N.; Sugawara, Y.; Nagata, R.; Kaneko, J.; Aoki, T.; Sakamoto, Y.; Hasegawa, K.; Kokudo, N.
<x xml:space="preserve">Abstract</x> Two hundred fifty‐three consecutive living‐donor liver transplant recipients with a right liver graft (RLG) were divided into three groups: an extended right liver graft (ERLG) group (n = 47) in which the middle hepatic vein (MHV) trunk was included in the graft, a modified right liver graft (MRLG) group (n = 114) in which the MHV tributaries were reconstructed with cryopreserved homologous veins and a simple RLG group (n = 92) in which the MHV tributaries were sacrificed. The volume of the anterior sector was significantly impaired in the RLG group compared to the other two groups, whereas the volume of the posterior sector was significantly improved in the RLG group, indicating that the impaired anterior sector regeneration by MHV deprivation was compensated by the posterior sector regeneration. The regeneration rate of the anterior sector was highest in the ERLG group (92%), moderate in the MRLG group (71%) and lowest in the RLG group (52%). The whole graft regeneration rate of the ERLG group was significantly higher than that of the other two groups. Poor regeneration, however, was not correlated with delayed functional recovery or long‐term outcome. Short‐term, the patency of reconstructed MHV tributaries was over 90%, but occlusion occurred frequently over the long‐term, especially in V5.